Causes and the Intensity of Workplace Bullying - Gunawan, Ria; Prihanto, Sutyas; Yuwanto, Listyo (Faculty of Psychology, Universitas Surabaya, 2009)
This study aimed to describe the problem of workplace bullying, the intensity, and its causing factors. This exploratory descriptive study was conducted through a survey of 123 participants working in Surabaya who experienced workplace bullying. The ques- tionnaire used to measure the intensity of the workplace bullying was an adaptation of Negative Act Questionnaire Revised (Matthiesen, 2000). The description, the intensity, and the causing factors of workplace bullying are discussed. Penelitian ini bertujuan mendeskripsikan masalah pembulian di tempat kerja (PTK= workplace bullying), intensitas PTK yang terjadi, dan faktor penyebab terjadinya PTK. Studi deskriptif eksploratif ini dilakukan dengan cara survei pada 123 partisipan yang bekerja di Surabaya dan mengalami PTK. Angket untuk mengukur intensitas PTK me- rupakan adaptasi angket Negative Act Questionnaire Revised (Matthiesen, 2000). Didiskusikan hasil penelitian tentang deskripsi, intensitas, dan faktor-faktor penyebab terjadinya PTK.